Adaptation by the Arctic Fox (Alopex lagopus) to the Polar Winter - Prestrud, Päl (ARCTIC, 1991)
In this article physiological, behavioural and morphological adaptations by the arctic fox to low temperatures and food scarcity in winter are discussed. The arctic fox (Alopex lagopus) adapts to the low polar winter temperatures as a result of the excellent insulative properties of its fur. Among mammals, the arctic fox has the best insulative fur of all. The lower critical temperature is below -40 degrees C, and consequently increased metabolic rate to maintain homeothermy is not needed under natural temperature conditions. Short muzzle, ears and legs, a short, rounded body and probably a counter-current vascular heat exchange in the legs contribute to reduce heat loss. A capillary rete in the skin of the pads prevents freezing when standing on a cold substratum. By seeking shelter in snow lairs or in dens below the snow cover and by curling up in a rounded position, expanding only the best-insulated parts of the body, the arctic fox reduces heat loss. The arctic fox copes with seasonal fluctuations in food supply by storing fat and caching food items during summer and fall. Saving energy through decreased activity and decreased basal metabolic rate might also be an adaptation to food scarcity in winter.Key words: arctic fox, basal metabolic rate, lower critical temperature, fat deposition, starvation Mots clés: renard arctique, taux de métabolisme basal, température critique inférieure, réserves de graisses, famine